Partial Sternotomy Due To Intrathoracic Foreign Body Suspected Implant Migration: A Case Report - Adrian Tangkilisan; Else Riahna; Wega Sukanto; Christha Zenithy Tamburian; Rigel Kent Paat (International Journal of Health and Pharmaceutical (IJHP), 2025)
Intrathoracic foreign bodies pose notable surgical challenges, particularly with concerns of implant migration. This case report details a 55-year-old male admitted to the ICU, exhibiting symptoms of coughing and hematemesis following partial sternotomy due to presumed implant migration. Comprehensive clinical assessment revealed stable vital signs and leukocytosis, but no signs of infection. The management strategy included a multidisciplinary approach encompassing infection control, wound care, and pharmacologic support. Partial sternotomy was performed, allowing for effective retrieval with minimized postoperative complications. Postoperative care emphasized respiratory support and regular monitoring of laboratory parameters to detect potential complications. The case underscores the importance of integrating traditional and innovative surgical techniques while prioritizing patient safety and health outcomes. Close monitoring and a tailored care plan were essential in managing the escalating symptoms and potential complications arising from the intrathoracic foreign body.